Analysis of Work Discipline, Work Motivation, Organizational Justice, and Their Influence on Employee Performance - Anas, Hafidz; Subiyanto, Didik; Yulianto , Eko (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the effect of work discipline, work motivation, and organizational justice on employee performance at DLHK DIY. A quantitative approach using questionnaires from 71 respondents and multiple linear regression analysis revealed that work discipline and motivation have a positive and significant effect, while organizational justice has a negative and insignificant effect. These findings offer strategic implications for improving employee performance through strengthened discipline and motivation.